İktisat ve edebiyat ilişkisini Gülten Akın şiirleri üzerinden anlamlandırma denemesi - Menteş, Duygu (My University, 2023)
Toplumsal bir bilim olan iktisat; üretim, tüketim, bölüşüm ve dağıtım ilişkilerini incelerken, temeline insanı ve toplumu alır. Sanat ve sanatın bir alanı olan edebiyat ise toplum içerisinde gelişen, insan ve toplumdan hareket ederek, birçok farklı alandan etkilenen ve bu etkiyi estetik unsurlar ile gösterebilen bir yapıya sahiptir. İktisadi dönemlerin edebiyat eserlerine nasıl yansıdığının incelenmesi, edebiyat ve iktisat arasında ilişki kurulmasında üzerine çalışılmasını gerektirecek özgünlüğe ve öneme sahiptir. Gülten Akın, yaşadığı toplumun iktisadi, siyasi, toplumsal değişimlerinden etkilenmiş büyük bir şairdir. 1950’den 1980 sonrasına Türkiye’nin iktisat politikaları odağında belirlenen dönemlerinin, Gülten Akın şiirleri üzerinden okunması çalışmanın amacını oluşturmaktadır

Economics is one of the fields of social sciences; while it is defined through the relations of production, consumption and distribution, it is based on people and society. On the other hand, literature is a branch of art that is affected by many different factors such as economy, politics and social. The aim of this master's thesis is to explain the relationship between economics and literature and to investigate how literary works are effected by economic periods. The aims and objectives of the thesis proposal can be explained as making sense of the relationship between economics and literature through Gülten Akın Poems. Gülten Akın is a poet who has a very important role in Turkish Literature and Turkish Poetry. It can be seen that Gülten Akın's works were influenced by the economy, the political currents of her period and social changes in the society, and she reflected these factors in her works.
An attempt to make sense of the relationship between economics and literature through Gülten Akın poems
Keywords: Akın, Gülten, 1933-2015; Economics and literature; Economics in literature; Edebiyat; Ekonomi ve edebiyat; Ekonomi, Edebiyatta; Gülten Akın; Gülten Akın Economics; İktisat; İktisat ve Edebiyat; Literature; Poem; Şiir; Turkey; Turkish poetry; Türk şiiri; Türkiye